WHEN RESOURCES ARE NOT ENOUGH: LOCAL KNOWLEDGE AS A KEY DRIVER OF SME’s PERFORMANCE - Ahmad Hafiyyan Shibghatalloh; Arisanti Ayu Wardhani; Hasan Aminda Syafrudin; Achmad Solechan; Albertus Setyo Sumargo; Lubertus Wahyu Priyo Dwiantoro (Universitas PGRI Semarang, 2025)
This study aims to examine the relationships between resources, local knowledge, and SME’s performance by integrating the Resource-Based View and Knowledge-Based View perspectives. A quantitative cross-sectional approach was employed using primary data collected through a structured questionnaire. The study was conducted among batik MSMEs in Pekalongan, Central Java, Indonesia. A purposive sampling technique was applied with specific criteria. A total of 100 MSMEs were selected as the research sample. Data analysis was carried out using (PLS-SEM) with SmartPLS. The results show that resources do not have a significant direct effect on MSME performance, indicating that resource availability alone is insufficient to improve business outcomes. However, resources have a significant positive effect on local knowledge, and local knowledge significantly influences MSME performance. Furthermore, the mediation analysis confirms that local knowledge fully mediates the relationship between resources and MSME performance.